2009
DOI: 10.3945/jn.108.100198
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Innate Immune Function Are Associated with Vitamin A Stores in Men

Abstract: Recommendations for vitamin A intake and liver stores are based on maintaining normal vision. We propose that higher levels may be required to maintain normal innate immune function. To test this hypothesis, we conducted an 8-wk residential study among 36 healthy Bangladeshi men with low vitamin A stores. Subjects were randomized to receive vitamin A (240 mg in 4 doses) or placebo during study wk 2 and 3. They received 2 vaccines during wk 5 and vitamin A stores were estimated by isotopic dilution at wk 8. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 57 publications
4
40
0
Order By: Relevance
“…In vitro and in vivo studies have shown that retinoic acid plays a key role in inhibiting the IL-6-and TGF-b-derived induction of proinflammatory Th17 cells in the gastrointestinal tract that results in the promotion of antiinflammatory Treg cells (37,38). Also, Ahmed et al (39) recently reported that liver vitamin A stores in Bangladeshi men were negatively associated with serum IL-6 and -17 concentrations. We hypothesized that the associations shown in our study between IL-6 and TNF-a concentrations and the increased resolution of ETEC infections in supplemented children may have resulted from the downregulation of the proinflammatory response and up-regulation of the Treg regulatory response by vitamin A.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that retinoic acid plays a key role in inhibiting the IL-6-and TGF-b-derived induction of proinflammatory Th17 cells in the gastrointestinal tract that results in the promotion of antiinflammatory Treg cells (37,38). Also, Ahmed et al (39) recently reported that liver vitamin A stores in Bangladeshi men were negatively associated with serum IL-6 and -17 concentrations. We hypothesized that the associations shown in our study between IL-6 and TNF-a concentrations and the increased resolution of ETEC infections in supplemented children may have resulted from the downregulation of the proinflammatory response and up-regulation of the Treg regulatory response by vitamin A.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A deficiency in rats leads to decreased natural killer (NK) 5 cell cytotoxicity after infection, partially explained by decreased NK cell numbers, whereas treatment with dietary retinoic acid, a bioactive metabolite of vitamin A, can restore NK cell numbers within 1 wk (5). In adult men, whole body vitamin A stores are positively associated with peripheral blood NK cell and NK T cell numbers (6). Vitamin A deficiency has profound effects on the antibody-mediated immune response.…”
Section: Historical Vitamin a And Immune Function Overviewmentioning
confidence: 99%
“…Although it is controversial whether PQQ is an essential coenzyme like vitamins for mammals, 30,31 this coenzyme, like others that cannot be synthesized in sufficient quantities by an organism, must be obtained from the diet to maintain fundamental systemic functions. [32][33][34][35][36][37] Therefore, we hypothesized that PQQ supplementation might prevent impaired GALT mass and function in mammals receiving PN administration regardless of its route, because the present PN solutions do not contain PQQ.…”
Section: Discussionmentioning
confidence: 99%